Pembelaan Terpaksa Melampaui Batas (Noodweer Exces) dalam Tindak Pidana Pembunuhan Begal Sebagai Upaya Perlindungan Diri - I Gede Windu Merta Sanjaya; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2022)
In facing the COVID-19, Indonesia had quite a lot of jobs that have been indirectly affected by the pandemic, causing an economic crisis. Economic crisis caused several people in the community to commit crimes, especially stealing with violence or referred to as begal. The thugs do not hesitate to persecute and even kill their victims in order to obtain the victim's property, so it’s necessary for the victim to protect himself from thugs so as not to incur material losses. In order for the perpetrator of the defense of the burglary to receive juridical protection, in implementation it must complete the elements and conditions of noodweer exces. Therefore, the purpose of the research is to discuss the regulation of the criminal act of noodweer exces beyond the limit in the crime of murder according to the Criminal Code (KUHP) and to analyze the criminal liability of the perpetrators of the crime of Noodweer exces against the perpetrators of the murder of robbers. This research uses a normative type of assessment, using a statutory approach and a conceptual approach. The sources of legal materials for this research consist of primary, secondary and tertiary sources of material. the results of the research explain that the regulation of Noodweer Exces according to article 49 paragraph (1) of the Criminal Code "Book of the Criminal Law" noodweer exces beyond the limit in purpose to a person is not convicted when taking a defense action in a state of necessity and accountability can not be asked if the perpetrator commits this action. with reasons of self-defense or nowdweer excess so that it can eliminate actions that are criminal in nature. Then in that case, it is necessary to know what is included in the noodweer action.